Omics in Clinical Practice 2014
DOI: 10.1201/b17137-19
|View full text |Cite
|
Sign up to set email alerts
|

Insights from Genomics into Bacterial Pathogen Populations

Abstract: Novel DNA sequencing techniques, referred to as "next-generation" sequencing (NGS), provide high speed and throughput that can produce an enormous volume of sequences with many possible applications in research and diagnostic settings. In this article, we provide an overview of the many applications of NGS in diagnostic virology. NGS techniques have been used for high-throughput whole viral genome sequencing, such as sequencing of new influenza viruses, for detection of viral genome variability and evolution w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 31 publications
0
52
0
2
Order By: Relevance
“…Furthermore, It has been shown that mutation errors in pyrosequencing reads tend to occur predominantly in homopolymeric regions (17,27). In the present study we did not assess the error rate of the present assay; however, others have estimated the overall error rate of the pyrosequencing technique to be on the average of 0.3% (12,28). It was also previously shown that the pyrosequencing error rate for detection of 17 known drug resistance mutations, located at homopolymer regions in the PR and RT genes of subtype B viruses, was Ͻ0.71% (17).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Furthermore, It has been shown that mutation errors in pyrosequencing reads tend to occur predominantly in homopolymeric regions (17,27). In the present study we did not assess the error rate of the present assay; however, others have estimated the overall error rate of the pyrosequencing technique to be on the average of 0.3% (12,28). It was also previously shown that the pyrosequencing error rate for detection of 17 known drug resistance mutations, located at homopolymer regions in the PR and RT genes of subtype B viruses, was Ͻ0.71% (17).…”
Section: Discussionmentioning
confidence: 42%
“…A later platform, the gene sequencer (GS) FLX pyrosequencing system is capable of producing 400 to 600 million bases per 10-h run (11). This technology also has a relatively long sequencing read length of 400 to 600 bp, which has the added advantage over the point mutation assays of being able to detect mutations in their sequence context and not just at a single locus (12).…”
mentioning
confidence: 99%
“…Furthermore, the available studies on WNV mutant spectrum diversification relied on Sanger sequencing methods (Deardorff et al, 2011;Jerzak et al, 2005Jerzak et al, , 2007Jerzak et al, , 2008, whereby a limited set of consensus sequences was obtained after a plaque-purification or molecular cloning step. Nextgeneration sequencing (NGS) technologies present an opportunity to deepen the analysis of RNA virus genetic variants (Barzon et al, 2011;Van Borm et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] This approach is cost effective and highly efficient for the recovery of viral genome sequences, taking advantage of the detection and characterization of viral genomes and viral metagenomics. 16,17 Sequence-independent, single-primer amplification (SISPA) is a methodology to synthesize and enrich viral genomes using random hexamer and SISPA sequences (5′-GCCGGAGCTCTGCAGATATC-3′). 18 SISPA NGS was used for defining RNA and DNA viruses including Rotavirus, Astrovirus, and Parvovirus.…”
Section: Introductionmentioning
confidence: 99%